A mediação de conflitos: uma possibilidade para formação continuada de professores na perspectiva da educação em direitos humanos - Santos, Maria de Fátima Ricardo dos (2019)
School violence has proven to be a public health and rights violation problem, insofar as it affects physical and mental integrity and the dignity of the human person, it produces processes of social discrimination, educational exclusion and human suffering. It is the school's social function, promoting personality development and sociability, guaranteeing equal access to schooling. The right to education for a culture of peace, democracy and human rights becomes a topic on the international human rights agenda, at a time when the world is experiencing serious violations of human rights. The manifestations of violence in different social and institutional spaces move citizens and nations to act in the name of life. At school, violence is expressed from the violation of fundamental rights, such as the right to education, whether in access, permanence and school success, to forms of physical and subtle, material and symbolic violence. The general objective of the research was to investigate conflict mediation as a possibility of educational action in the field of education in and for human rights in the continuing education of teachers of basic education. The specific objectives were intended to: conceptualize the contemporary understanding of the problem of violence in and of the school and its manifestations in the school context, impacting life, school culture and the teaching and learning process, object of the Decade of the culture of Peace; contextualize the decade and the national policy on human rights education in order to dialogue with the National Guidelines for Teacher Education and the experiences of school mediation; to investigate conflict mediation as one of the axes of training for education in and for human rights, based on the experience of the “At school with respect” project. The present work comprises a bibliographic and documentary research with a focus on the project developed within the continuous training carried out with municipal schools in João Pessoa and other municipalities, focusing on indiscipline and the prevention of violence at school. The research proves the relevance of school mediation as a teacher training strategy with a view to preventing violence and promoting a culture of peace, human rights and democratic citizenship at school.